Jarcho-Levin syndrome with diastematomyelia and a dorsal dermal sinus - Raja Tamiru, MD; Tesfahunegn Hailemariam, MD; Amanuel Aboye, MD; Bethel Germamo, MD; Yodit Abraham, MD; Erko Chala, MD; Samuel Sisay Hailu, MD (Radiology Case Reports, 2024)
Jarcho-Levin syndrome (JLS) is a congenital dysostosis characterized by multiple vertebral and intrinsic rib abnormalities. JLS and neural tube abnormalities rarely occur together. There have been few cases of JLS associated with a split spinal cord malformation (diastematomyelia). A dorsal dermal sinus is a tract from the skin that may end in soft tissue, epidural space, or most commonly intradural. We report the case of a 5-day-old male neonate with JLS who presented with respiratory distress immediately after birth. A chest radiograph revealed multiple bilateral asymmetric rib deformities and irregular rib fusions, multi-level segmentation defects of the thoracic vertebrae, and associated dextroconvex scoliosis of the thoracic spine. He was subsequently diagnosed with diastematomyelia, a dorsal dermal sinus, and tethered cord on ultrasound. The infant succumbed to respiratory distress from superimposed pneumonia. JLS is rarely associated with distematomyelia, and there are only ten reports worldwide. We presented the eleventh case of JLS with type 2 diastematomyelia. In addition, this is the first reported case of co-occurrence with a dorsal dermal sinus.